The relationship of one-sided chewing with status Dental and oral hygiene in the community Age 30-40 years Lingkungan Simae Baranti Sub-district, Sidrap Regency - utari (Sahabat Publikasi Kuu, 2024)
Chewing food with one side of the mouth will cause thick and strong muscles only on that side. The facial muscles on the right and left sides will become asymmetrical. Chewing one side is one of the bad habits that can affect the hygiene status of teeth and mouth. Dental and oral hygiene can be measured by an index with good, medium, bad criteria. The measurement used is with OHI-S (oral hygiene index simplified).. This study aims to determine whether there is a one-sided chewing relationship with dental and oral hygiene status in people aged 30-40 years, Simae Environment, Baranti District, Sidrap Regency. This type of research is descriptive correlative with a cross sectional approach. Sampling was carried out using purposive sampling techniques and obtained 44 respondents. The results of the correlative descriptive test showed that there was a relationship between one-sided chewing and OHI-S status in people aged 30-40 years, Simae Environment, Baranti District, Sidrap Regency, namely chewing using one side by 72.7% of medium criteria.